A conceptual framework to analyse the multiscalar politics of education for sustainable peacebuilding. Issue 4 (1st October 2016) - Lopes Cardozo, Mieke T.A.; Shah, Ritesh
ABSTRACT: A critical and more nuanced understanding of the multifaceted relationship between projects of peacebuilding and educational provision is starting to develop. Drawing on an epistemological and ontological anchor of critical realism, and a methodology informed by the application of cultural political economy analysis and the strategic relational approach to understanding educational discourses, processes and outcomes, we illustrate how the 'many faces' of education in conflict-affected situations can be better theorised and conceptually represented. In doing so, we link goals of peacebuilding to those of social justice, and reinvigorate the notion of education playing a transformative rather than a restorative role in conflict-affected contexts. Making such ideas concrete, we provide examples of how such an analytical framework can be employed to understand the multi-faceted relationship between education and projects of social transformation in conflict-affected environments across the globe.